Thursday

April 24, 2014

April 24, 2014

Posted by **Robert** on Friday, November 16, 2012 at 3:04pm.

- HELP ! Algebra -
**Steve**, Friday, November 16, 2012 at 3:15pm-x^2 + 6x + 10 = 0

-(x^2 - 6x) + 10 = 0

-(x^2 - 6x + 9) + 10 + 9 = 0

-(x-3)^2 + 19 = 0

(x-3)^2 = 19

x-3 = ±√19

x = 3±√19

**Related Questions**

algebra - solve the quadratic equation by completing the square -3x^2+9=1

Algebra - I was given this answers to a problems I solved but I do not ...

Algebra - I was given this answers to a problems I solved but I do not ...

algebra - Solve the quadratic equation by completing the square. -3x^2+9x=1 Not ...

algebra II - I'm quite clueless as to how to solve this. I know the quadratic ...

Algebra - How do I solve a quadratic equation x^2 - x = 30 by completing the ...

Algebra - Which is the easiest way to figure a quadratic equation; graphing, ...

Algebra Quadratic Equations - I am trying to define the different appraoches to ...

Algebra 2 - Completing the square method allows you to solve any quadratic ...

Algebra - How do you solve an equation with a fraction like x^(2/3) +13=17. I ...